Socioeconomic inequalities in human papillomavirus knowledge and vaccine uptake: evidence from a cross-sectional study in China - Gong, Xiaoqian; Xu, Jing; He, Yuzhen; Zou, Guofang; Liu, Jing (Frontiers in Public Health, 2024)
Providing the human papillomavirus (HPV) vaccine is effective to eliminate the disparity in HPV-related cancers. It is unknown regarding inequality in the distribution of HPV vaccination in China since the vaccine was licensed and approved for use in 2016. This study aimed to examine socioeconomic inequalities in HPV-related knowledge and vaccination and identified factors associated with such inequalities. Methods: Self-administered questionnaires measuring HPV-related knowledge and vaccine uptake were completed by 1306 women through online survey platform. HPV knowledge was assessed using a 12-item question stem that covered the hazards of HPV infection, HPV vaccine dosage, benefits, and protection. Cluster analysis by combining monthly household income, educational level, and employment status was used to identify socioeconomic status (SES) class. The concentration index (CI) was employed as a measure of socioeconomic inequalities in HPVrelated knowledge and vaccination. Linear regression and logistic regression were established to decompose the contributions of associated factors to the observed inequalities.The CI for HPV-related knowledge and vaccine uptake was 0.0442 and 0.1485, respectively, indicating the higher knowledge and vaccination rate were concentrated in groups with high SES. Education and household income made the largest contribution to these inequalities. Age, residency and cervical cancer screening were also important contributors of observed inequalities.Socioeconomic inequalities in HPV-related knowledge and vaccination uptake are evident in China. Interventions to diffuse HPV-related information for disadvantaged groups are helpful to reduce these inequalities. Providing low or no-cost HPV vaccination and ensuring accessibility of vaccines in rural areas are also considered to be beneficial.